(untitled) (Singapore; San Francisco, Calif., USA, 1995)
This book major is introduction about issues and comparative perspectives (some key development issues for transitional,..); Country studies such as econimic reform in viet nam: achivements and prospects,...
Keywords: Asia,Châu Á; Economic conditions,Điều kiện kinh tế